Rheology profiles of gelling agents for food and pharmaceutical applications - Abdul Rahman, Mohammad Nasrin; Almurisi, Samah Hamed; Mawazi, Saeid Mezail; Chatterjee, Bappaditya; Doolaanea, Abd Almonem (IIUM Press, International Islamic University Malaysia, 2017)
Rheology of gelling agents is important for the formulator in both food and pharmaceutical industry. In pharmaceutical industry, gelling agent s are widely used in liquid preparations, semisolid preparations and even in solid formulations. They are used to increase the viscosity, stabilise the formulation and control drug release. Most of these uses stem from the rheological properties of the gelling agent. The idea of this work came after we tried to formulate a semisolid formulations, topical and for oral use. We tried to find the rheological profiles of different gelling polymer in order to choose the one that best fits our need. However, we found lack in the data available in the literature. Thus, the best way was to screen wide range of gelling agents and study their rheology in some details. After that, each formulator can choose the one that suits the application. This work describes the rheological profiles of different gelling agents without discussing their suitability for specific application. The reason is that each application needs different properties. We hope that the data presented here give good guidance to the formulator to choose the suitable gelling agent for the intended formulation